Fungsi Institusi Pendidikan dalam Upaya Sosialisasi Pencegahan Kekerasan Seksual dan Pelecehan Seksual pada Anak (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2023)
Sexual violence and child abuse have become serious and widespread issues in school and adolescent environments. This phenomenon has physical, psychological, sexual, and social impacts on the victims. Involvement of the government, society, and educational institutions, as well as legal efforts and socialization, is crucial in preventing and addressing this issue. The main objective of this community service is to provide awareness about protection and create a sense of security for children, while also striving to enhance the role of families through socialization conducted by educational institutions. The method employed in this event is through face-to-face socialization by introducing the basic legal concepts used by the government to prohibit "mudik" (homecoming travel). The event involves students from SMP Al Falah Tlajung. The outcome of this service is that laws such as the Sexual Violence Crime Act (UU TPKS) have been enacted to regulate actions and sanctions against perpetrators. Socialization, education, and community involvement are also key elements in combating sexual violence and child abuse. Awareness of children's rights, prevention efforts, and collective roles can shape a safe and protected environment for children.